Comparing the Effectiveness of Dialectical Behavior Therapy and Acceptance and Commitment Therapy on Psychological Flexibility in Mothers of Children with Learning Disabilities - Zahra Shafeie; Mohammad Ghamari; Aboutaleb Saadati Shamir (Iranian Journal of Educational Research)
Objective: The present study was carried out with the objective of examining the comparative efficacy of dialectical behavior therapy and acceptance and commitment therapy in enhancing psychological flexibility among mothers of children diagnosed with specific learning disabilities. Methods: This study utilized a semi-experimental design comprising pre-test, post-test, and a follow-up assessment after three months. The target population consisted of mothers of children with learning disabilities enrolled in the fifth grade of elementary schools in Tehran in 2022. A purposive sample of 60 participants who met the specified criteria was randomly allocated into three groups of 20 individuals each. Data collection involved the utilization of the Dennis and Vanderwal cognitive flexibility questionnaire, while data analysis was conducted using mixed analysis of variance. Results: The findings indicated a significant improvement in psychological flexibility scores following both dialectical behavior therapy and acceptance and commitment therapy (P<0.001). Furthermore, the results demonstrated a superior effectiveness of acceptance and commitment therapy compared to dialectical behavior therapy. Conclusions: In light of these results, professionals in the fields of psychology and counseling are advised to consider implementing these educational and therapeutic approaches to enhance the psychological flexibility of mothers raising children with specific learning disabilities.